EFFECT OF TUTORING ON ACADEMIC ACHIEVEMENT OF MINORITY ADOLESCENTS IN A LOW SOCIOECONOMIC AREA - Johnson, Adam Clarke (East Carolina University, 2019)
There are a number of studies that focus on how minority students are negatively impacted by the effects of stereotype threat. Black students are typically the most noted group of students affected. I hypothesized that tutoring could be an especially effective method of providing support to minority students when tutors employ a client-centered approach consistent with Motivational Interviewing (MI). The purpose of this study is to examine whether the academic achievement (measured by class grades) of the students involved in the study improved following a MI-informed tutoring intervention focused on building self-efficacy.
Keywords: Minority students; Academic achievement; Motivational interviewing; Tutors and tutoring